Respiratory Physiology: Gas Exchange and Regulation of Breathing (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Respiratory physiology explains the fundamental mechanisms by which the body ensures continuous uptake of oxygen and elimination of carbon dioxide to sustain cellular metabolism and acid–base balance. Effective respiration depends on the integration of pulmonary ventilation, alveolar gas exchange, blood transport of respiratory gases, and precise neural and chemical regulation of breathing. This article provides a comprehensive overview of the physiological principles governing gas exchange in the lungs and the control systems that regulate breathing patterns under resting and stressed conditions. Particular emphasis is placed on the structural and functional organization of the respiratory system, diffusion processes across the alveolar–capillary membrane, and the role of central and peripheral regulatory mechanisms. Understanding these processes is essential for interpreting normal respiratory function and for recognizing the physiological basis of respiratory disorders. Adequate respiration depends on the continuous renewal of alveolar air and the efficient transfer of respiratory gases between the external environment and circulating blood. This process is governed by coordinated mechanical activity of the thoracic structures and finely regulated control systems that adapt breathing to metabolic requirements. The balance between oxygen uptake and carbon dioxide removal determines cellular energy production and acid–base equilibrium. An integrated view of these mechanisms highlights respiration as a dynamic and responsive system essential for physiological stability.